AN INVESTIGATION OF THE ENGLISH TEACHING IN A TERTIARY INSTITUTION A CASE STUDY - Nurrohmi, - (2007)
his study was concerned with the English teaching program in a tertiary institution implementing a social work education in West Java, Indonesia covering: (1) the teaching materials, (2) the methods, (3) the students' needs in the English teaching. The participants involved were two female English lecturers, 10 students in the first semester, academic year 2002, taken from two classes, 10 non-English lecturers, and five authorities in the research site. This study used a case study for the researcher wanted to explore a single case concerning the English teaching in a tertiary institution in the academic year 2002. To get detailed information, a variety of data collection procedures were conducted, i.e., observations, interviews, documents, and questionnaires. This study aimed to identify the teaching materials provided for the students, the methods used by the lecturers, and to find out the students' needs in the English teaching. The results indicated that there was not teaching materials supplied by the institution.The types of materials commonly provided by the lecturers were a kind of course book/textbook generated by the lecturer, and the authentic materials. Materials taught are four major skills, grammar, vocabulary, pronunciation, and translation. The lecturers used various methods: the students were asked to practice their speaking and listening through dialogue in English, asking and answering a question in English, and through English presentation; to practice their reading and writing through English paper presentation and writing paragraphs about their daily activities and past life. Interviews data revealed that the students need a course book practical and easy to study in which materials content relates to social work profession, and the emphasized skills are reading and speaking. Moreover, data from questionnaire indicated that reading and writing should be emphasized.It is recommended that to apply the ESP both English lecturers in the research site should consider writing the teaching materials based on the needs analysis. To understand the limitations of the English teaching in a tertiary institution implementing professional education, further research with longer period of observation, accurate methodology, along with the high researcher's sensitivity on the related issues, is needed.